2021
DOI: 10.1111/lre.12391
|View full text |Cite
|
Sign up to set email alerts
|

Water hyacinth (Eichhornia crassipes) infestation cycle and interactions with nutrients and aquatic biota in Winam Gulf (Kenya), Lake Victoria

Abstract: Lake Victoria, like many other lakes in Africa, is affected by water hyacinth that reside in several bays for the majority of the year. The weed affects several economic activities of the local communities and denies revenue to the government from blue economic activities related to the lake. The present study examined the interaction of water hyacinth with biotic and abiotic factors and the efficiency of introduced weevils to better control this invasive weed. Water quality samples were collected and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Wondim, Mosa, and Alehegn 2016; Dersseh et al 2020; Enyew, Assefa, and Gezie 2020; Ayele and Atlabachew 2021b; Damtie, Mengistu, and Meshesha 2021; Dersseh et al 2022), who studied three shallow bays along the Lake Tana shoreline and reported the highest eutrophication in the agriculture-impacted bays due to invasion of the wetlands and inshore lake by water hyacinth. The ndings also agree with studies carried out in other African Lakes, for example, in the Lake Kyoga basin of Uganda byObubu et al (2022), Lake Victoria of Kenya byOtieno et al (2022), in Lake Victoria of Uganda byWanda et al (2015), and in the African Great Lakes(Plisnier et al 2022). …”
supporting
confidence: 90%
“…Wondim, Mosa, and Alehegn 2016; Dersseh et al 2020; Enyew, Assefa, and Gezie 2020; Ayele and Atlabachew 2021b; Damtie, Mengistu, and Meshesha 2021; Dersseh et al 2022), who studied three shallow bays along the Lake Tana shoreline and reported the highest eutrophication in the agriculture-impacted bays due to invasion of the wetlands and inshore lake by water hyacinth. The ndings also agree with studies carried out in other African Lakes, for example, in the Lake Kyoga basin of Uganda byObubu et al (2022), Lake Victoria of Kenya byOtieno et al (2022), in Lake Victoria of Uganda byWanda et al (2015), and in the African Great Lakes(Plisnier et al 2022). …”
supporting
confidence: 90%
“…Attempts to control E. Crassipes by various biological, chemical or mechanical methods, either separately or in combination, have exhibited limited success (Malik, 2007;Otieno et al, 2021). The use of different insect species, fungal pathogens and allelopathic plants as biocontrol agenda does not result in significant reductions in E.…”
Section: Submerged Macrophytes Transplantationmentioning
confidence: 99%
“…In many cases, such invasive aquatic plants were originally intentionally introduced for such purposes as horticulture and aquarium trade. Freshwater ecosystems, however, are generally vulnerable to such introductions, with potentially severe consequences, including treats to biodiversity, decreasing water quality and quantity, productivity and recreational benefits of a lake (reviewed by Koutika & Rainey, 2015; Otieno et al, 2021). As a result to there are numerous alien invasive aquatic weeds problematic in many parts of the world, this review only discusses two of the most damaging tropical weeds, namely, E. crassipes and S. molesta .…”
Section: Biomanipulation To Control Algal Bloomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water hyacinth thrives in nutrient-rich waters (Coetzee and Hill, 2012) and its growth may also be promoted by increased temperatures due to climate change (You et al, 2014). The degradation of ecosystem services related to water hyacinth invasion are reviewed elsewhere (Ongore et al, 2018: Otieno et al, 2022, and include its impairment of boat navigation (Güereña et al, 2015), its creation of habitat for dangerous animals (e.g., snakes, hippos) and vectors of infectious diseases [e.g., mosquitoes (Chandra et al, 2006;Minakawa et al, 2012;Crossetti et al, 2019) and snails (Masifwa et al, 2001)], potential stimulation of greenhouse gas production (Kosten et al, 2016;though see Oliveira-Junior et al, 2018), and its support of anoxia in bottom waters. And, water hyacinth is costly to remove (Yan et al, 2017;Wainger et al, 2018).…”
mentioning
confidence: 99%